Earthworm surface casts affect soil erosion by runoff water and phosphorus transfer in a temperate maize crop - Le Bayon, Renée-Claire; Binet, Françoise (My University, 2001)
To test the hypothesis that earthworm surface casts contribute to soil erosion and nutrient transfers in a temperate maize crop, two rainfall experiments were set up. One was focused on the erodibility of earthworm casts, the second examined in how casts affect water runoff and nutrient transfers. Casts produced from anecic and endogeic earthworm species were both analyzed. Visual observations in the field showed no cast transport but only cast disintegration and transfers of particles. Erodibility of newly deposited casts was high and differed significantly between age groups. Cast erosion was significantly positively related to initial mass when young but not when old. The paradox is that despite a high cast abundance (25% of the area) and obvious cast erosion, amounts of sediment and nutrient losses (C, N and P) in the runoff were at least twice as high without, than in the presence of, surface casts. Earthworm activities were shown to act as a physical brake for soil erosion by (i) creating a surface roughness with the deposition of surface casts and (ii) reducing water runoff by associated enhanced water percolation. Once the breaking-down point of the physical resistance of casts was reached, all surface casts were quickly disintegrated and finally completely washed away. The amount of particulate phosphorus recovered in water runoff was 34.7 mg P m−2, while 128.5 mg P m−2 was estimated to have been released from casts. The transfers were found to occur over a short-distance through successive deposition/suspension of soil particles in the water runoff.
Keywords: Earthworm; surface casts; simulated rainfall; soil erosion; phosphorus